التوصيف المورفولوجي لبعض الطرز المحلية من الورد الشامي ((Rosa damascena Mill. وورد النسرين (Rosa canina L.) - نصّور مازن; عبد القادر أحمد; عباس سوسن (Latakia University Journal -Biological Sciences Series, 2019)
يهدف هذا البحث إلى إجراء التوصيف المورفولوجي ودراسة درجة التباين والقرابة بين عدد من الطرز المحلية من الورد الشامي والورد البري، حيث تم استخدام 28 صفة مظهرية للتمييز بين الطرز المدروسة. مكنت بعض الاختلافات المظهرية مثل كثافة الأشواك، لون الأوراق، شكل الزهرة والثمرة بتمييز أنواع الورد الثلاثة المدروسة والتي أعطت بحسب نتائج التحليل العنقودي أكبر نسبة اختلاف بين الطرز والأنواع المدروسة ( حوالي 40%). كما أشارت النتائج إلى وجود درجة تباين منخفضة جداً بين طرز النوع الواحد وبخاصة الموجودة في المنطقة نفسها والتي وصلت في حدودها القصوى إلى 7%، لذلك كان من الصعب التمييز بشكل مظهري بين هذه الطرز الوراثية حتى مع وجود فروقات شكلية، لأنها قد تكون ناتجة عن الظروف البيئية. This research aims at studying the morphological characterization and the evaluation of variability and relationship of some Rosa damascena and rosa canina genotypes. Twenty-eight morphological traits have been employed to discriminate between the genotypes studied. According to the observations made, there were some morphological differences in prickle density, leaf color, fruit and flower shape that allow differentiation between the three rose species studied with distance value 40%. The results of this study have shown a low level of diversity among the rose genotypes presented in the same region (maximum 7%), so it was very difficult to distinguish morphologically between these genotypes despite the existence of morphological differences which most probably could be caused by environmental conditions.